Thinking without the 'circle': Marine plastic and global ethics. (July 2015) - Mitchell, Audra
Abstract: Marine plastic has received significant attention as a spectacle of consumer waste and ecosystemic fragility, but there has been little discussion of its ethical implications. This essay argues that marine plastic poses a direct challenge to the basic frameworks of global ethics. These frameworks are dominated by the image of the 'circle', an abstract boundary intended to separate 'humanity' from the rest of the universe and insulate it against harm. However, this article argues that marine plastic undermines the 'circle' in two ways. First, it embodies conditions of 'hyper-relationality', including entanglement and the properties of toxicity, that penetrate the boundaries of 'the circle'. Second, it exerts 'forcefulness', but at scales that radically exceed the dominant spatio-temporal dimensions of 'the circle'. By virtue of these features, marine plastic thoroughly penetrates the boundaries of 'the circle', making it impossible to expel harm beyond its boundaries. Although this essay focuses on marine plastic, its core argument can also be fruitfully applied to other phenomena that share similar material, scalar, spatio-temporal and relational features (for instance, atmospheric particulate, nuclear waste and nitrate pollution). The essay concludes by exploring the alternative ethical possibilities that marine plastic and similar phenomena prompt: in particular, a responsive ethos based on a sense of shared vulnerability and exposure. Graphical abstract: Image from the 'Gyre' Installation by Audra Mitchell and Liam Kelly, University of Queensland, Brisbane, Australia, March 2014. Highlights: Liberal-cosmopolitan ethics is imagined as a 'circle' that insulates humans from harm. It functions by attempting to expel harm outside of its boundaries. Marine plastic possesses properties – hyper-relationality and forcefulness – that undermine 'the circle'. It, and phenomena that share these features, directly challenge the dominant bases of global ethics. I present an alternative ethos based on responsiveness to the elements of hyper-relationality and forcefulness.